2020
DOI: 10.1002/ajoc.202000153
|View full text |Cite
|
Sign up to set email alerts
|

DABCO‐Mediated [4+1] Cycloaddition of β,β‐Dihalo Peroxides with Sodium Azide toward Isoxazoles

Abstract: The isoxazole skeleton is one of key structural motifs, which displays widespread applications in drugs, agriculture, and synthetic intermediates. Herein, we disclose the DABCO‐mediated [4+1] cycloaddition of β,β‐dihalo peroxides and sodium azide for synthesis of multisubstituted isoxazoles. The cycloaddition proceeds through the formation of N−C and N−O bonds. This method shows excellent regioselectivity and good scalability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In 2020, Li et al reported a DABCO-mediated approach toward multisubstituted isoxazoles that proceeded via defluorination cycloaddition of β,β-difluoro peroxides with sodium azide (Scheme 29). 58 Compared to their precedent (Scheme 11) with cobalt catalysis under heating, these transformations were performed in a relatively mild fashion. In the products of this reaction, susceptible substituents including carbalkoxy, amide, benzoyl, phosphoryl, and heteroaryl groups could be installed at R 3 position.…”
Section: Polyfluoroalkyl Peroxidementioning
confidence: 99%
“…In 2020, Li et al reported a DABCO-mediated approach toward multisubstituted isoxazoles that proceeded via defluorination cycloaddition of β,β-difluoro peroxides with sodium azide (Scheme 29). 58 Compared to their precedent (Scheme 11) with cobalt catalysis under heating, these transformations were performed in a relatively mild fashion. In the products of this reaction, susceptible substituents including carbalkoxy, amide, benzoyl, phosphoryl, and heteroaryl groups could be installed at R 3 position.…”
Section: Polyfluoroalkyl Peroxidementioning
confidence: 99%
“…In 2020, the preparation of a wide range of multisubstituted isoxazoles 33 was reported with sodium azide 1 as nitrogen source by Li et al (Scheme 6) [26] A broad scope of β,β-dihalo peroxides 29 reacted with sodium azide 1 under catalysis of DABCO in acetonitrile at 80 °C. All products 33 were obtained in low to good yields (31-89 %) with excellent regioselectivity except two derivatives which showed very low yields (R 1 = Alkyl, R 2 = H, R 3 = CO 2 Et, 7 % yield and R 1 = Ph, R 2 = H, R 3 = C 3 H 7 , 13 % yield).…”
Section: Isooxazolesmentioning
confidence: 99%